Consequences of Hypothyroidism on Auditory System Function in Tshr Mutant (hyt) Mice - Sprenkle, Pamela M. (Springer-Verlag, 2001)
The otological consequences of hypothyroidism and the outcome of thyroxin (T4) administration during the developmental period preceding the onset of hearing were examined in mice that express a point mutation in the gene encoding the thyrotropin receptor (Tshr), the so-called hyt mouse. Progeny of sires homozygous for the trait and heterozygous dams were injected with T4 or saline placebo from birth through the tenth postnatal day and auditory-evoked brainstem responses (ABRs) to acoustic clicks and tone bursts were recorded from young adults. Mutant (hyt/hyt) mice exhibited a distinctive pattern of sensory pathology that was characterized by their insensitivity to sound, prolonged response latencies, reduced peak amplitudes, and steep latency-intensity curves relative to the phenotypically normal, euthyroid, +/hyt littermates. Following thyroxin treatment, hyt/hyt mice responded to acoustic stimuli more frequently, were more sensitive to tone bursts throughout their audiometric range, and exhibited decreased latencies and increased amplitudes when compared with placebo-treated homozygous mutants. Although thresholds to acoustic stimuli were improved relative to the untreated group, T4-treated homozygotes were less sensitive than normal, euthyroid individuals. In addition, energy consumption by auditory brainstem nuclei, measured by 2-deoxyglucose (2-DG) uptake, was significantly lower in hyt/hyt mice compared with heterozygotes, and T4 treatment increased the level of 2-DG utilization. Moreover, mean ages for eye-opening and pinna-raising were delayed in animals that were homozygous for the hyt allele. When T4 was administered to hyt/hyt animals, pinna-raising occurred earlier than in untreated animals. A subset of homozygotes exhibited circling behavior, indicative of vestibular and/or motor dysfunction, even though all individuals assumed a normal righting reflex. These findings, including recruitment-like behavior and the restoration of response magnitude at high levels but not low, suggest that the cochlear amplifier is the primary locus of an enduring otological defect associated with hypothyroidism in the Tshr mouse.